New High-Speed Rail Lines and Market Competition: Short-Term Effects on Services and Demand in Italy. Issue 1 (January 2015) - Cascetta, Ennio; Coppola, Pierluigi
The new 1, 000 km of high-speed rail (HSR) line between Turin and Salerno, Italy, were completed in 2009, and new service by the Italian railways state-owned company Trenitalia started in December of that year. Furthermore, in anticipation of the European open-access regulatory framework, starting from April 2012, the new HSR private operator Nuovo Trasporto Viaggiatori entered the market and is competing with the incumbent Trenitalia. This is the first case of large-scale competition between nonsubsidized HSR operators on the same line (i.e., infrastructure managed by the state-owned company, Rete Ferroviaria Italiana). This study provides an overview of the short-term dual effects of the opening of the new HSR line operating with a single service provider (between 2010 and 2012) and of the competition between the two operators starting from 2012. Before-and-after effects on services, prices, and attracted and generated demand based on several data sources, including ad hoc surveys and a system of mathematical models, are presented. Results suggest that the dual effect of new HSR lines and the opening of competition in the market has been producing a significant increase in HSR supply (+94% of trains per day) and demand (+98% of passenger-kilometers per year). The market share in the HSR core area increased about 20% at the expense of air and automobile modes. About 13.8 million extra trips per year were estimated in 2013 with respect to rail demand in 2009 (8.3 million diverted from other modes and 5.5 million induced trips) despite the severe economic crisis faced by the country in the same period.